Implementation of Teachers' Professional Allowance (TPG) Credit: A Case Study of Non-Performing Loans at PT BPR Aruna Nirmaladuta Gianyar - Kurniawan, I Gede Agus; Oktaviani. M, Masrianti; Budiana, I Nyoman; Mahadewi, Kadek Julia (International Journal of Business, Law, and Education, 2025)
The development of Indonesia’s economy cannot be separated from the role of financial institutions, particularly Rural Banks (Bank Perkreditan Rakyat/BPR), which focus on financing the lower-middle-income sectors. One of BPR’s featured products is the Teacher Professional Allowance (TPG) credit, which uses teachers’ certification allowances as collateral for repayment. This study examines the implementation of TPG credit at PT BPR Aruna Nirmaladuta, analyzes the factors contributing to non-performing loans, and explores the legal measures taken to resolve them. The research employs an empirical legal method with statutory, conceptual, and field approaches through interviews and document studies. The findings indicate that TPG credit defaults are influenced by internal factors, such as inadequate creditworthiness analysis, and external factors, such as delays in the government’s disbursement of the TPG funds. Resolution efforts are conducted through restructuring, mediation, and litigation to ensure legal certainty and protection for both parties.